Analisis Penerapan SAK ETAP pada Penilaian Persediaan Metode FIFO UD Siti Aminah - Lailia Ananda Putri; Waloyo Waloyo (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the conformity of SAK ETAP (Financial Accounting Standards for Entities Without Public Accountability) implementation regarding the FIFO (First-In, First-Out) inventory valuation method at UD Siti Aminah in Surabaya. The data examined consists of inventory stock cards from March 2023. This research employs a case study design with a mixed-methods approach, integrating qualitative analysis with quantitative data from UD Siti Aminah’s inventory records. Data collection was conducted through observation, in-depth interviews, and documentation of secondary data. The data was processed using descriptive analysis techniques. The results indicate that the inventory valuation at UD Siti Aminah for the May 2023 period had not yet implemented valuation methods aligned with SAK ETAP, specifically the chapters governing inventories.